2014
DOI: 10.11114/jets.v3i3.753
|View full text |Cite
|
Sign up to set email alerts
|

Articulating Teachers’ Expectations afore: Impact of Rubrics on Chinese EFL Learners’ Self-Assessment and Speaking Ability

Abstract: Under the constraint of classroom time, English as foreign language (EFL) learners usually do not have adequate opportunity to practice oral English in class nor receive individualized feedback from the instructor. After-class practice constitutes an essential component of foreign language learning. This study investigated the effect of utilizing rubrics on EFL learners' oral English using a 16-week experiment and a questionnaire. A total of 61 college students participated in the study, 41 in the rubric-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Not surprisingly, positive perceptions of self-assessment were typically developed by students who actively engaged the formative type by, for example, developing their own criteria for an effective self-assessment response (Bourke, 2014), or using a rubric or checklist to guide their assessments and then revising their work (Huang and Gui, 2015;Wang, 2017). Earlier research suggested that children's attitudes toward self-assessment can become negative if it is summative (Ross et al, 1998).…”
Section: Student Perceptionsmentioning
confidence: 99%
“…Not surprisingly, positive perceptions of self-assessment were typically developed by students who actively engaged the formative type by, for example, developing their own criteria for an effective self-assessment response (Bourke, 2014), or using a rubric or checklist to guide their assessments and then revising their work (Huang and Gui, 2015;Wang, 2017). Earlier research suggested that children's attitudes toward self-assessment can become negative if it is summative (Ross et al, 1998).…”
Section: Student Perceptionsmentioning
confidence: 99%